KAJIAN KARAKTERISTIK FISIK DAN MEKANIK BIJI KEMIRI SUNAN (Reutealis trisperma Blanco) - SARIFAH NURJANAH (Bionatura, 2018)
Kemiri sunan contains vegetable oil which can be used as raw material of biodiesel. The oil can be extracted from the kemiri sunan kernel. In designing of oil press machine, physical and mechanical characteristics of kemiri sunan are needed. This study aims to examine the physical and mechanical characteristics of kemiri sunan kernel in some moisture content. Experimental method used in this research with t test. Physical and mechanical characteristics of kemiri sunan shell and kernel were studied on 5 levels of water content ie 3%, 5%, 7%, 9% and 11% with 7 replication. Physical and mechanical characteristics were roundness, spericity, density, volume, porosity, angle of repose and compressive strength. The results showed that increasing water content increased shell roundness from 0.886 - 0.905 and kernel roundness from 0.852 - 0.865; the shell spericity increased from 0.838 - 0.865 and the kernel spericity from 0.768 - 0.846; shell volume increased from 4.506 – 5.686 cm3 and kernel volume from 2.224 – 2.764 cm3; shell mass density decreased from 1.002 - 0.999 g / cm3 and kernel mass density from 1.003 to 0.998 g / cm3; shell bulk density increased from 0.299 - 0.342 g / cm3 and kernel bulk density from 0.385 - 0.441 g / cm3; shell porosity increased from 46.03 - 47.57% and kernel porosity from 46.00 - 46.60%; the shell angle of repose increased from 31.29 - 35.29o and the kernel angle of repose from 37.86 - 42.00o; increased shell compressive strength from 21.95 - 27.24 N and kernel compressive strength from 8.89 - 26.95 N.